Some like it hot: Preference for temperature and pungency consumption is associated with sensitivity to noxious heat - Defrin, Ruth; Dekel-Steinkeller, Michal; Urca, Gideon (European journal of pain, 2021)
Individuals vary in their temperature and pungency preferences; whereas some individuals prefer to bath in, or consume food and beverages at very high temperatures, others prefer lukewarm temperatures. Similarly, pungent food may be preferred by some, but not by others. The aim was to investigate, for the first time whether temperature and pungency preferences are associated with variations in thermal sensitivity or ethnic origin related to pungency consumption. 115 healthy volunteers participated. The thresholds for warm (WST) and heat-pain (HPT) sensations were measured over the tongue and dorsal hand, and the participants' preferred drinking and bath temperatures were measured. In addition, data on the participants' ethnic background as well as temperature and pungency preferences and household habits regarding eating, drinking and bathing were collected. The reported drinking and bathing preferences correlated significantly with the measured drinking and bath temperatures, respectively, validating subjects' reports. Tongue and hand HPT, but not WST, correlated with both the reported and the measured drinking and bathing preferences, as well as with pungency preferences. Neither ethnic origin nor gender affected HPT or temperature preferences; however, males preferred a greater level of spiciness than females. The association of the reported and measured preferences with noxious heat sensitivity in both relevant and irrelevant body regions, and lack of an ethnicity effect may suggest that these qualities are innate. The association of HPT and spiciness preferences correspond with the mutual activation of the tongue vanilloid receptors by noxious heat and capsaicin. People vary with regard to their temperature and spiciness preferences for reasons yet unknown. The study revealed that these preferences correlate with one another and were associated with the sensitivity to noxious heat but not with age, gender and cultural background, which suggests that they may be innate.